2020
DOI: 10.1242/dev.181669
|View full text |Cite
|
Sign up to set email alerts
|

Auxin fluxes through plasmodesmata modify root-tip auxin distribution

Abstract: Auxin is a key signal regulating plant growth and development. It is well established that auxin dynamics depend on the spatial distribution of efflux and influx carriers on the cell membranes. In this study, we employ a systems approach to characterise an alternative symplastic pathway for auxin mobilisation via plasmodesmata, which function as intercellular pores linking the cytoplasm of adjacent cells. To investigate the role of plasmodesmata in auxin patterning, we developed a multicellular model of the Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 73 publications
5
85
0
Order By: Relevance
“…Recently, passive auxin diffusion via plasmodesmata, intercellular pores that linking the cytoplasm of adjacent cells, was shown to markedly improve the accuracy of simulated auxin distribution patterns in the root apical meristem 35 . Therefore, it will be of interest to evaluate the contribution of symplastic connectivity between the radial layers of the root to prebranch site formation and LR spacing.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, passive auxin diffusion via plasmodesmata, intercellular pores that linking the cytoplasm of adjacent cells, was shown to markedly improve the accuracy of simulated auxin distribution patterns in the root apical meristem 35 . Therefore, it will be of interest to evaluate the contribution of symplastic connectivity between the radial layers of the root to prebranch site formation and LR spacing.…”
Section: Discussionmentioning
confidence: 99%
“…1B). In the context of auxin, this was recently highlighted in Mellor et al (2020). The authors, focusing on the root tip of Arabidopsis, compared the observed signal intensity of a DII-VENUS reporter (where fluorescence negatively correlates with auxin concentration) (Brunoud et al, 2012) with that predicted by a modified computational model of them (Band et al, 2014).…”
Section: Types Of Movement Auxin Might Experience Across Pd and Theirmentioning
confidence: 99%
“…Symplastic auxin movement indeed reduced the sharpness of concentration differences and provided better agreement with those observed experimentally. Specifically, this form of movement was essential to facilitate reflux from the high auxin areas in the outer tissues, where active transporters direct flow shoot-ward, to the inner central tissues where flow is root-ward and the auxin concentration is lower (Mellor et al, 2020). This reflux component was theorised in Grieneisen et al, 2007 and is necessary to retain high auxin concentrations in the root tip, something necessary for many biological processes.…”
Section: Types Of Movement Auxin Might Experience Across Pd and Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, PIN2 also localizes on the tip-facing and inner sides at the DEZ, contributing to an auxin reflux from the shootward stream back into the tip-directed stream [ 54 ]. An alternative cell-to-cell transport via plasmodesmata also enables auxin reflux to the root tip and its accumulation in cells of the quiescent-center and upper columella layers [ 55 ].…”
Section: Gravity Signal Transduction In the Root Statocytesmentioning
confidence: 99%